2021
DOI: 10.3389/fncom.2021.629380
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Exploration and Exploitation Balance in the Silkmoth Olfactory Search Behavior by Information-Theoretic Modeling

Abstract: Insects search for and find odor sources as their basic behaviors, such as when looking for food or a mate. This has motivated research to describe how they achieve such behavior under turbulent odor plumes with a small number of neurons. Among different insects, the silk moth has been studied owing to its clear motor response to olfactory input. In past studies, the “programmed behavior” of the silk moth has been modeled as the average duration of a sequence of maneuvers based on the duration of periods witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Accordingly, there is a problem that the original search performance of living things cannot be replicated. For this reason, different kinds of research have been carried out more recently and applied to the bio-inspired algorithm, such as information-theoretic analysis of the trajectory of an insect ( Hernandez-Reyes et al, 2021 ), extraction of adaptability from neuroethology data by fuzzy inference ( Shigaki et al, 2020 ), and the acquisition of behavioral switching indices in response to environmental changes by measuring insect behavior while visualizing airflow ( Demir et al, 2020 ). In the current study, we found that behavioral modulation occurred based on the relationship between the direction of the odor arrival and the wind, and we used our data to reproduce a behavioral trajectory that was not only better than that of the conventional bio-inspired algorithm but was also more similar to the search behavior of the actual silkmoth.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is a problem that the original search performance of living things cannot be replicated. For this reason, different kinds of research have been carried out more recently and applied to the bio-inspired algorithm, such as information-theoretic analysis of the trajectory of an insect ( Hernandez-Reyes et al, 2021 ), extraction of adaptability from neuroethology data by fuzzy inference ( Shigaki et al, 2020 ), and the acquisition of behavioral switching indices in response to environmental changes by measuring insect behavior while visualizing airflow ( Demir et al, 2020 ). In the current study, we found that behavioral modulation occurred based on the relationship between the direction of the odor arrival and the wind, and we used our data to reproduce a behavioral trajectory that was not only better than that of the conventional bio-inspired algorithm but was also more similar to the search behavior of the actual silkmoth.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior offers an interesting research topic in regard to motor-cognitive function: how is such successful locomotion achieved under conditions of turbulent odor plumes, utilizing the insects’ small number of neurons. Hernandez-Reyes et al (2021) measured the behavior of moths using a virtual reality system that presents accurate and reproducible odor stimuli by using blue light and optogenetic moths. Their results demonstrate that behavioral variations have a higher probability of obtaining more information than “programmed behaviors” (i.e., reactive, exploitative behaviors), suggesting that silk moths incorporate some stochasticity into their behavior in order to balance the exploration and exploitation of the acquired information.…”
Section: Biological Inter-limb Coordinationmentioning
confidence: 99%